Cultural adjustment experiences challenges and, coping strategies of Somali refugees in Malaysia : counseling implications - Abdinoor, Noor Mohamed (Institute of Education, International Islamic University Malaysia, 2012)
Immigration trends in this century represent a significant force in shaping populations around the world. This thesis focused on exploring the experiences of Somali refugees in Malaysia. The primary purpose of this study was to investigate the cross-cultural challenges and adjustment strategies of the Somali refugees in Malaysia. Somalis are among the largest groups of refugees in Malaysia. The rapid increase in their population was as a result of the political instability, civil wars and droughts that have ravaged the entire nation of Somalia for almost two decades. Employing the qualitative approach of phenomenology the study used semi-structured interviews to collect data on the lived experiences of 10 Somali refugees in Malaysia. The interviews were recorded, transcribed and analyzed into themes related to the experienced difficulties, and coping mechanisms. Six challenges were identified: namely, financial difficulties, communication barriers, social isolation/exclusions, technology difficulty, security concerns and difficulties related to food and dress codes. Four coping mechanisms emerged from the analysis; learning about the new culture, experiences from previous cultural contacts, financial support from family, tolerance and patience. Moreover, motivating factors identified are support from friends and relative and being optimistic for change. The counseling implications from these findings for the delivery of guidance and counseling services to refugees in general and to Somali refugees in Malaysia in particular are discussed. Thus the findings will be useful to counselors, social workers, and other professionals dealing with refugees. The study is hoped to contribute, on a wider level, to the on-going efforts of cross-cultural counseling in the field of counseling and psychotherapy. Furthermore, the findings and recommendations of the study will be useful to the Governments, organizations that provide assistance and training to refugees, as well as other departments like health, education and the security.